Os municípios paulistas vistos como cidades inteligentes: verificação do serviço gratuito de internet como ferramenta de informação - Cramolichi, Stanley Cabral (2024)
Context: The term “Smart City” has become more recurrent in recent years to qualify cities that, using technology, promote intelligent, strategic, and participatory management. From this perspective, the internet emerges as a crucial tool in the integration between the citizen, the city, and the public authorities as it serves as a viable means for data flow and democratic access to information. Justification: The complexity of the “Smart City” concept, the fact that the title of “smart city” is self-declared, and, moreover, the socioeconomic and spatial segregation of citizens necessitate a critical analysis of the services provided to the population to justify such a title. Objective: In this sense, the work aims to evaluate the effectiveness of the public service of free internet access provided by cities considered Smart Cities in the state of São Paulo, looking at connectivity as a means of accessing information. Method: Three municipalities from three different mesoregions of São Paulo were analyzed regarding the spatial distribution of internet access points. Data related to connection quality were collected in the field using monitoring software executed on a notebook and a smartphone. The multiple case study method and qualitative analysis of obtained data were applied. Results: The results enabled a comparison between access points and municipalities, which highlighted the inefficient distribution of internet access points and, in some situations, the total unavailability of the service to residents. The discussion points to the fragility of the technological infrastructure aimed at information and communication in Brazilian municipalities, which disadvantages more vulnerable regions of the cities and weakens the concept of smart cities.